Periodic Monitoring Report on the Status of Board-Endorsed Independent Evaluation Office Recommendations and Management Implementation Plans. (Policy Papers; Policy Paper ;, 2007)
IEO evaluations are an integral part of the Fund's learning culture, helping the Fund absorb lessons that improve its work. In addition, the objectivity of IEO evaluations has bolstered the Fund's credibility. In discussing the report of the External Evaluation of the IEO (the 'Lissakers report'), Executive Directors welcomed the suggestions to strengthen follow-up to the IEO recommendations?including more Board involvement-and supported a more systematic approach for following up and monitoring the implementation of IEO recommendations approved by the Board. This periodic monitoring report (PMR) is the first such effort under the new procedures approved by the Executive Board in January 2007. In particular, it responds to the instruction that 'Management shall present to the Board a periodic monitoring report on the state of implementation of actions contained in the forward-looking implementation plans already in force and not deemed completed on the occasion of a prior periodic monitoring report. These reports shall indicate difficulties in implementing the original plan and propose remedial or substitute actions whenever appropriate. The first periodic monitoring report shall be prepared following the delivery of the 2007 IEO Annual Report. As the IEO Annual Reports cover the status of all past IEO recommendations, it is expected that the first periodic monitoring report produced by Management would also review the implementation of recommendations made to date.'.